2009
DOI: 10.1093/jjco/hyp039
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral Metastases with High Risk of Symptomatic Malignant Spinal Cord Compression

Abstract: Vertebral metastases with lamina involvement tended to cause symptomatic MSCC. Latent development of MSCC occurred more frequently in the MTS compared with other levels of the thoracic and the cervical spine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Husband et al analyzed the association between sensory function and MRI findings; however, relationship between imaging features and motor function was not widely investigated (12). A study by Hamamoto et al implied that lesions with lamina involvement tend to cause motor deficits more frequently than lesions without (13). None of these reports To our knowledge, the present study is the first study to demonstrate an association between symptoms classified according to the Frankel scale and the MRI-assessed extent of spinal metastases using both qualitative parameters and quantitative measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Husband et al analyzed the association between sensory function and MRI findings; however, relationship between imaging features and motor function was not widely investigated (12). A study by Hamamoto et al implied that lesions with lamina involvement tend to cause motor deficits more frequently than lesions without (13). None of these reports To our knowledge, the present study is the first study to demonstrate an association between symptoms classified according to the Frankel scale and the MRI-assessed extent of spinal metastases using both qualitative parameters and quantitative measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative neurologic status is also related to overall survival [26]; in particular, normal neurologic function at admission predicts higher survival and patients with Frankel Grade E at admission have a higher median survival compared with those with Frankel Grades A to D. Hosono et al also showed a correlation between patient preoperative neurologic status or prognosis and survival [25]. Nonetheless, not all patients tend to recover neurologically in the same fashion after palliative surgery when affected by metastatic epidural spinal cord compression [7,23]. In general, metastatic epidural spinal cord compression can occur acutely after vertebral collapse or slowly after impairment of venous drainage leading to intramedullary vasogenic edema and eventually irreversible spinal cord necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Prospective multicentric cohort studies are required to confirm these findings and identify prognostic factors. Neoplastic pachymeningitis can be suspected preoperatively by the use of current imaging modalities such as contrast-enhanced MRI [20] and by medical history of a slowly progressive neurological impairment in absence of vertebral collapse [23], but both the surgeon and the patient should be aware that the diagnosis is more often performed intraoperatively. Appropriate statements about the risk of neurologic worsening or absence of recovery could be added to the informed consent and improve patient awareness of complications related to palliative surgical decompression.…”
Section: Discussionmentioning
confidence: 99%
“…SCC can precipitate immediately, such as in impact injuries, or take months or years to develop, such as in tumors or secondary to wear and tear of the spine. Generally, the most common symptoms of SCC are back pain, limb paralysis, sensory loss, urinary and fecal incontinence or urinary retention, sphincter dysfunction, sexual dysfunction, autonomic nervous system dysfunction, and loss of spinal cord function ( 2 , 3 ). SCC is clinically present in 5-14% of patients with cancer during the progression of their malignancy, and 2-5% of patients with cancer have at least one episode of compression within their final 2 years of life ( 4 ).…”
Section: Introductionmentioning
confidence: 99%